Dynamics of Establishment of the Enterprises and the Entrepreneurship in Romania - Angheluță, Petrică Sorin; Negescu Oancea, Mihaela Diana; Diaconu, Amelia; Dima, Cristina (European Journal of Sustainable Development, 2020)
The prosperity of a society is influenced by the existence of an industrial base. The stronger the industrial base, the more the society is considered to be more prosperous. A high degree of enterprises competitiveness leads to jobs that favor business development. The entrepreneurial spirit contributes to the development of businesses. For Romania, the article presents the evolution of the indicators regarding the degree of establishment of the newly created active companies. Also, the dynamics of the activity of newly created active enterprises in Romania is addressed. The level of education and the age of the founder differ depending on the activity sector of the newly created active enterprise. From the evolution analyzed, it can be concluded that, in Romania, the profile of the investor is represented by an individual under the age of 40, a high school graduate or who has university studies. For Romania, in recent years, the number of newly created active enterprises has decreased in the trade sector. Also, the sector with the highest dynamics in terms of setting up and closing companies, is the agriculture, forestry and fisheries sector. These aspects are important for the economy, but also for the studies of the analysis of the training needs. In the process of generating new sources of economic growth, a relevant contribution is provided by the degree to which the entrepreneurial culture is promoted. Keywords: entrepreneurship, sustainable development, Romania